A randomized controlled trial of antibody response to 2019–20 cell-based inactivated and egg-based live attenuated influenza vaccines in children and young adults. Issue 5 (31st January 2022) - Williams, Katherine V.; Zhai, Bo; Alcorn, John F.; Patricia Nowalk, Mary; Levine, Min Z.; Kim, Sara S.; Flannery, Brendan; Moehling Geffel, Krissy; Jaber Merranko, Amanda; Nagg, Jennifer P.; Collins, Mark; Susick, Michael; et al.
Abstract: Background: Hemagglutination inhibition (HAI) titers to the live-attenuated influenza vaccine (LAIV4) are typically lower than its counterpart egg-based inactivated influenza vaccines (IIV). Similar comparisons have not been made between LAIV4 and the 4-strain, cell-culture inactivated influenza vaccine (ccIIV4). We compared healthy children's and young adults' HAI titers against the 2019–2020 LAIV4 and ccIIV4. Methods: Participants aged 4–21 years were randomized 1:1 to receive ccIIV4 (n = 100) or LAIV4 (n = 98). Blood was drawn prevaccination and on day 28 (21–35) post vaccination. HAI assays against egg-grown A/H1N1, A/H3N2, both vaccine B strains and cell-grown A/H3N2 antigens were conducted. Primary outcomes were geometric mean titers (GMT) and geometric mean fold rise (GMFR) in titers. Results: GMTs to A/H1N1, A/H3N2 and B/Victoria increased following both ccIIV and LAIV and to B/Yamagata following ccIIV (p < 0.05). The GMFR range was 2.4–3.0 times higher for ccIIV4 than for LAIV4 (p < 0.001). Within vaccine types, egg-grown A/H3N2 GMTs were higher (p < 0.05) than cell-grown GMTs [ccIIV4 day 28: egg = 205 (95% CI: 178–237); cell = 136 (95% CI:113–165); LAIV4 day 28: egg = 96 (95% CI: 83–112); cell = 63 (95% CI: 58–74)]. The GMFR to A/H3N2 cell-grown and egg-grown antigens were similar. Pre-vaccination titers inversely predicted GMFR. Conclusion: The HAI response to ccIIV4 was greater than LAIV4 in this study of mostly older children, and day 0 HAI titers inversely predicted GMFR for both vaccines. Lower prevaccination titers were associated with greater GMFR in both vaccine groups.